2014
DOI: 10.1007/s00299-014-1676-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated signaling networks in plant responses to sedentary endoparasitic nematodes: a perspective

Abstract: Sedentary plant endoparasitic nematodes can cause detrimental yield losses in crop plants making the study of detailed cellular, molecular, and whole plant responses to them a subject of importance. In response to invading nematodes and nematode-secreted effectors, plant susceptibility/resistance is mainly determined by the coordination of different signaling pathways including specific plant resistance genes or proteins, plant hormone synthesis and signaling pathways, as well as reactive oxygen signals that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 142 publications
1
34
0
Order By: Relevance
“…tomato, have an effector repertoire that enables them to interact with all known major signaling pathways to activate the SA signaling pathway by sabotaging its activators and stimulating its repressor (171). In addition, some root-feeding nematodes secrete chorismate mutase (CM) involved in SA biosynthesis and manipulate lipid signaling involved in JA-induced defense (47,93). Consequently, local manipulation of defense hormone signaling pathways by phytophages may attenuate systemic induced defense responses to other plant feeding organisms, either within or across compartments.…”
Section: Systemic Induction and Manipulation Of Transcriptional Changmentioning
confidence: 99%
See 1 more Smart Citation
“…tomato, have an effector repertoire that enables them to interact with all known major signaling pathways to activate the SA signaling pathway by sabotaging its activators and stimulating its repressor (171). In addition, some root-feeding nematodes secrete chorismate mutase (CM) involved in SA biosynthesis and manipulate lipid signaling involved in JA-induced defense (47,93). Consequently, local manipulation of defense hormone signaling pathways by phytophages may attenuate systemic induced defense responses to other plant feeding organisms, either within or across compartments.…”
Section: Systemic Induction and Manipulation Of Transcriptional Changmentioning
confidence: 99%
“…Root feeding by sedentary endoparasitic nematodes results in the production and accumulation of SA, JA, and ET at the site of infection (67). Subsequently, transcriptional reprogramming results in the activation of the core defense system involving SA/JA/ET-mediated pathways (80,93,168). For example, in A. thaliana, cyst nematode-induced JA-mediated defense depends on the protein phosphatase AP2C1, which is a negative regulator of the mitogen-activated protein kinases MPK3 and MPK6, two positive regulators of plant defense responses controlling ET and JA biosynthesis (140).…”
Section: Nematode-induced Systemic Defense Pathwaysmentioning
confidence: 99%
“…Transcriptome and microarray analyses of host roots infected with plant nematodes showed differential changes in the expression of genes responding to several hormones including auxin, ethylene (ET), jasmonic acid (JA), salicylic acid (SA), brassinosteroids (BR), gibberellins (GA), and abscisic acid (ABA)222324. A number of studies have indicated that the signaling pathways of SA, JA, BR, ABA, and ET are involved in the defense response of host plants to nematodes252627282930. Auxin, ET and GA have also been reported to play a positive role in the early stages of development of nematode feeding cells313233.…”
mentioning
confidence: 99%
“…Rapid production of ROS in the apoplast by RBOHD is an early defence response that occurs after the successful recognition of pathogens by the plant immune system, and that can kill pathogens, trigger hypersensitive cell death, activate the expression of defence‐related genes and interact with plant signalling networks to modulate local and systemic immunity (Apel and Hirt, ). Studies in several different plant species have also indicated that ROS play important roles in plant–nematode interactions (Li et al ., ). In certain compatible interactions, nematodes appear to utilize effector molecules to manipulate ROS levels and to suppress effective defence responses in the host plant (Dubreuil et al ., ; Lin et al ., ; Siddique et al ., ), whereas, in other interactions, ROS activation contributes to basal defences or is associated with incompatibility (Kandoth et al ., ; Kong et al ., ; Melillo et al ., ; Teixeira et al ., ).…”
Section: Discussionmentioning
confidence: 97%